IMPLIKASI YURIDIS STRATEGI FLASH SALE OLEH PELAKU USAHA E-COMMERCE - Firlli Wijaksana; Rosalinda Elsina (Gapenas Publisher, 2023)
The author writes this journal to review and examine the flash sale strategy by e-commerce business actors whether it fulfills the predatory pricing element as stipulated in Article 20 of Law No. 5 of 1999 concerning prohibition of monopoly practices and unfair business competition (hereinafter referred to as Law no. 5 of 1999) or not, because in practice flash sales are used as a strategy by e-commerce business actors almost fulfilling the elements of predatory pricing practices in which the implementation of the flash sale promotion strategy uses setting prices on a product below the average market price with limits the time and product given to attract consumers to get to know the shop of the e-commerce business actors and this is felt to undermine the justice of e-commerce business actors who will enter the market but only have small capital. Because there is no provision regarding the flash sale strategy, the authors interested in studying the problem m using normative juridical research methods using legal approaches and approaches. The results of this study found that the flash sale strategy can be classified as a form of predatory pricing if the elements in Article 20 of Law No. 5 of 1999 are taken as a whole. It is necessary to prove it using the rule of reason approach and other tests such as above-cost tests and limits. pricing strategy. If an e-commerce business actor is proven to have engaged in predatory pricing practices, administrative sanctions in Article 6 paragraph (2) points c, f, and g of PP No. 44 Year 2021